A soft, bioinspired artificial lymphatic system for interactive ascites transfer - Peng Wang; Ji Fu; Peng Jin; Jin Zeng; Xiaohui Miao; Heling Wang; Yinji Ma; Xue Feng (Wiley, 2023)
Abstract Low‐flow removal of refractory ascites is critical to treating cirrhosis and digestive system tumor, and thus, commercial ascites pump emerged lately. The rigid structure of clinically available pumps rises complication rate and lack of flow rate monitoring hinders early warning of abnormalities. Herein, a soft artificial system was proposed inspired by lymph for interactive ascites transfer with great biocompatibility. The implantable system is composed of pump cavity, valves and tubes, which are soft and flexible made by silica gel. Therefore, the system possesses similar modulus to tissues and can naturally fit surrounding tissues. The cavity with magnetic tablet embedded is driven by extracorporeal magnetic field. Subsequently, the system can drain ascites with a top speed of 23 mL min−1, much higher than that of natural lymphatic system and state‐of‐art devices. Moreover, integrated flexible sensors enable wireless, real‐time flow rate monitoring, serving as proof of treatment adjustment, detection and locating of malfunction at early stage. The liver function of experimental objects was improved, and no severe complications occurred for 4 weeks, which proved its safety and benefit to treatment. This artificial lymphatic system can serve as a bridge to recovery and pave the way for further clinical research.